Biochemical analysis of human eIF4E-DCP2 interaction: Implications for the relationship between translation initiation and decapping - Zachary F. Mandell; Jeff Coller (PLoS ONE, 2025)
All eukaryotic mRNAs bear a 7-methylguanosine cap on their 5’ end. The 5’ cap enables mRNA translation by binding directly to eIF4E; which further recruits other factors and the 40S ribosome. Additionally, the 5’ cap maintains transcript stability; removal of the cap by the enzyme Dcp2 is necessary to degrade the mRNA. An a priori conclusion, therefore, has been that cap binding by eIF4E and DCP2 are antithetical to each other as both need access to the same substrate, i.e., the 5’ cap. In this study, we purified native full-length human eIF4E and Dcp2 and utilize biophysical and biochemical approaches to examine the in vitro interplay between Dcp2 and eIF4E. We confirm that Dcp2 is sufficient to remove the 5’ cap. Moreover, we demonstrate that Dcp2 binds RNA with nanomolar affinity. We discovered that, unexpectedly, eIF4E does not interfere with Dcp2’s decapping function, contradicting previous mechanistic models. Moreover, eIF4E binding appears to increase the affinity of Dcp2 for RNA. Although limited to in vitro conditions, our findings warrant a reevaluation of the proposed relationship between these mRNA cap-binding proteins.